Intelligent teambuilding in the context of teaching a foreign language - Tatyana Grigorievna Gokzhaeva (Вестник Майкопского государственного технологического университета, 2023)
The article deals with the factor of intellectual teambuilding as a tool for effective team building and its orientation to the joint and coordinated implementation of communicative tasks in the process of teaching a foreign language. Teaching a foreign language in the mode of intellectual team building involves competent guidance of the teacher to ensure the development and improvement of skills of constructive communication in the format of a polylogue, improving reading skills and understanding of practice-oriented texts in the context of CLIL-technologies, as well as providing the basic elements of psychological and emotional comfort in the classroom, clear setting goals and determining methods for achieving them, involvement of trainees in joint coordinated work with the simultaneous development of integrative mechanisms and the potential of each student. The concept of polylogue and the role of the factor of team building in the process of improving the skills of oral speech, increasing motivation and providing high emotional tone classes. The role and position of the teacher is considered as a factor determining the nature of the relationship of students in the group. The importance of professional qualities of the teacher, a departure from the formal approach to the conduct of classes, the attitude to each student as a unique person are fundamental. The aspect of the organization of group interaction in the process of teaching foreign languages involves intensive contact between all members of the group with the teacher and each other, the cultivation of intra-group norms of relations, trust in communication, providing feedback of motivation, reducing the social distance, contributing to the ultimate goal of learning a foreign languagееducation of the subject of communication of a new generation. Analysis of the results of teaching a foreign language with the use of intellectual teambuilding allows us to say that this technique contributes to the activation of creative team thinking and effective learning of language material.